Anchoring the mission: A framework for understanding mission maintenance in professional service firms. Issue 3 (September 2022) - Loscher, Georg J.; Kaiser, Stephan
Abstract: Mission maintenance in professional service firms must balance the commercial and professional logics and prevent mission drift. Based on a case study of 'auditing in action' in a German professional service firm we argue that mission maintenance results from interactions between the practice and field level. We find that anchors on the field level target individuals' discretionary choices by balancing competing demands from the commercial and professional logics on the practice level. Therefore, we identify anchoring as a central cross-level mechanism for maintaining the balance between routinizing for professional quality and 'flexibilizing' for efficiency on the practice level. With these findings we make two contributions to the literature: an analysis of how the field level can contribute to maintaining organisations' missions in fields that have competing logics, and the identification of anchoring as a central mechanism to balance competing demands with the expectations of referent audiences on the field level. Highlights: Mission maintenance is facilitated by anchors. Anchors are part of the field's infrastructure. Anchoring balances flexibilizing and routinizing and thereby hinders mission drift. Mission maintenance is a result of vertical and horizontal dynamics at the field and practice level.